Large-Scale Nutrient Dynamics in the Baltic Sea, 1970–2016 - Savchuk, Oleg P. (Frontiers in Marine Science, 2018)
The Baltic Sea is one of the world’s marine areas well covered by both long-term observations and oceanographic studies. It is also a large coastal area in which eutrophication had already been recognised half a century ago. While the mechanisms of eutrophication are largely understood, several features are less recognised and sometimes neglected, including: a) natural and anthropogenic North-South and East-West nutrient gradients within the drainage basin and marine ecosystems; b) the compensatory potential of the interconnectivity between the Baltic Sea basins; c) long nutrient residence times and high buffer capacity of the system, resulting in slow responses to nutrient load reductions. Particularly important is the interaction of d) naturally occurring saltwater inflows sporadically ventilating deep water layers and e) a partly man-made intensification of biological oxygen consumption. Resulting redox alterations of biogeochemical nitrogen and phosphorus cycles are locked in a “vicious circle” that promotes cyanobacterial nitrogen fixation, thereby hindering nitrogen load reduction and sustaining an elevated trophic state. This tight coupling of natural environmental variation and human impacts complicates both scientific studies and management recommendations. Our primary objective is to describe all these features and mechanisms with the best available data on nutrient loads, and unique estimates of the basin-wide nutrient pools. These data are presented as both long-term time series and empirical nutrient budgets. The analysis is supplemented by results of biogeochemical modelling. A second, more practical objective is to make these time series available to the community.